Strong asymmetry of hemispheric climates during MIS-13 inferred from correlating China loess and Antarctica ice records - Z. T. Guo; A. Berger; Q. Z. Yin; L. Qin (Copernicus Publications, 2009)
We correlate the China loess and Antarctica ice records to address the inter-hemispheric climate link over the past 800 ka. The results show a broad coupling between Asian and Antarctic climates at the glacial-interglacial scale. However, a number of decoupled aspects are revealed, among which marine isotope stage (MIS) 13 exhibits a strong anomaly compared with the other interglacials. It is characterized by unusually positive benthic oxygen (δ 18 O) and carbon isotope (δ 13 C) values in the world oceans, cooler Antarctic temperature, lower summer sea surface temperature in the South Atlantic, lower CO 2 and CH 4 concentrations, but by extremely strong Asian, Indian and African summer monsoons, weakest Asian winter monsoon, and lowest Asian dust and iron fluxes. Pervasive warm conditions were also evidenced by the records from northern high-latitude regions. These consistently indicate a warmer Northern Hemisphere and a cooler Southern Hemisphere, and hence a strong asymmetry of hemispheric climates during MIS-13. Similar anomalies of lesser extents also occurred during MIS-11 and MIS-5e. Thus, MIS-13 provides a case that the Northern Hemisphere experienced a substantial warming under relatively low concentrations of greenhouse gases. It suggests that the global climate system possesses a natural variability that is not predictable from the simple response of northern summer insolation and atmospheric CO 2 changes. During MIS-13, both hemispheres responded in different ways leading to anomalous continental, marine and atmospheric conditions at the global scale. The correlations also suggest that the marine δ 18 O record is not always a reliable indicator of the northern ice-volume changes, and that the asymmetry of hemispheric climates is one of the prominent factors controlling the strength of Asian, Indian and African monsoon circulations, most likely through modulating the position of the inter-tropical convergence zone (ITCZ) and land-sea thermal contrasts.